The Influence of Intellectual Capital and Information Technology on Sustainable Competitive Advantage - Ahmad Tohir; Mochamad Purnomo (Universal Business and Management Review, 2025)
This study aims to analyze the influence of intellectual capital and information technology on sustainable competitive advantage (SCA) at PT PLN (Persero) Distribution Central Java and the Special Region of Yogyakarta. Both variables are considered strategic factors in strengthening the company's competitiveness amid the challenges of digitalization and changes in the energy industry landscape. The method used was a quantitative approach, including multiple linear regression analysis, and data collection via questionnaires distributed to 83 active employees at PT PLN UID Jateng-DIY. The results of the study show that both partially and simultaneously, intellectual capital and information technology have a positive influence on sustainable competitive advantage. This reflects the importance of organizational knowledge management and the application of appropriate technology in supporting sustainable competitive advantage. The limitation of this study lies in the general scope of the respondents, which does not fully represent the specific role of information technology within the work units that directly manage it. Therefore, further studies are recommended to refine the segmentation of respondents, ensuring results that are more representative and in-depth.